Study on the best time of refracturing for Hancheng coal seam - Wei WANG; Haifeng ZHAO; Liang JI; Chaowei WANG; Zhengzhao ZHANG; Xuejie XING (Meikuang Anquan)
The old wells in Hancheng Block face the problem of production decline after long-term exploitation, and need to be re-fractured to form new fractures to communicate with CBM rich areas, so as to achieve stable CBM production. Due to the small difference of initial stress in coal seam, the magnitude and direction of in-situ stress change significantly after fracturing and long-term drainage, which directly affects the choice of re-fracturing time. Therefore, we firstly obtain the initial ground stress of well Y3 in the research block combined with logging data, then simulate the change of coal seam ground stress during fracturing by using finite element model, then study the change of pore pressure during drainage and production, and determine the horizontal principal stress and induced stress according to the steering mechanism of refracturing, so as to obtain the best time for refracturing. Field tests were carried out on well Y3. It is found that the stress produced by the first fracturing in coal seam has little influence and does not cause stress reversal. After about 1 500 days of drainage, the difference of non-uniformity of pore pressure is about 0.6 MPa, which is equal to the difference of initial in-situ stress in the coal seam section, that is, the stress direction reverses. Secondary fracturing at this time is conducive to generate new fractures that can extend 70 m near the hole and communicate the CBM rich area at the bottom of the hole; according to the method proposed in this paper, the daily gas production of well Y3 increased from 114 m3 to 1 626 m3 after the same zone re-fracturing, and the effect is remarkable.